Om de af Dr. Boucherie foreslaaede Midler til at give Træ en større Varighed. - Lütken, Ch. (Tidsskrift for Landøkonomi, 2018)
Om de af Dr. Boucherie foreslaaede Midler til at give Træ en større Varighed.